PERKEMBANGAN DAN DAMPAK FINANCIAL TECHNOLOGY TERHADAP INKLUSI KEUANGAN DI INDONESIA: STUDI LITERATUR - Aswirah, Aswirah; Arfah, Aryati; Alam, Syamsu (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This literature review explores the development of Financial Technology (FinTech) and its impact on financial inclusion in Indonesia. The study reveals significant growth in the FinTech sector, driven by increased internet penetration, smartphone usage, and supportive government policies. FinTech innovations, such as digital payment systems and peer-to-peer (P2P) lending, have expanded access to financial services for underserved populations, particularly in rural areas. However, challenges remain, including digital divides and the need for robust consumer protection regulations. The findings suggest that while FinTech has enhanced financial inclusion, addressing these challenges is crucial for sustainable growth. The study concludes with recommendations for improving regulatory frameworks and promoting collaborations between FinTech companies and traditional financial institutions to further drive financial inclusion in Indonesia.